2019
DOI: 10.1029/2019gc008628
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Cracks and Frozen Flow in Oceanic Lithosphere Inferred From Electrical Anisotropy

Abstract: Geophysical observations of anisotropy in oceanic lithosphere offer insight into the formation and evolution of tectonic plates. Seismic anisotropy is well studied but electrical anisotropy remains poorly understood, especially in the crust and uppermost mantle. Here we characterize electrical anisotropy in 33 Ma Pacific lithosphere using controlled-source electromagnetic data that are highly sensitive to lithospheric azimuthal anisotropy. Our data reveal that the crust is ∼18-36 times more conductive in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 60 publications
1
9
1
Order By: Relevance
“…Although our core‐scale measurements do not show a systematic correlation in resistivity in the discrete orientations, recent active‐source electromagnetic measurements have shown a clear electrical anisotropy in the oceanic lithosphere, whereby conduction at crustal depths is enhanced in a direction subparallel to the paleo mid‐oceanic ridge (Chesley et al, 2019). Fisher (1998) noted that the permeability of oceanic crust varies extensively due to the presence of fractures, and cannot simply be determined from core measurements.…”
Section: Comparison With a Hydrological Model And Other Oceanic Drillcontrasting
confidence: 59%
“…Although our core‐scale measurements do not show a systematic correlation in resistivity in the discrete orientations, recent active‐source electromagnetic measurements have shown a clear electrical anisotropy in the oceanic lithosphere, whereby conduction at crustal depths is enhanced in a direction subparallel to the paleo mid‐oceanic ridge (Chesley et al, 2019). Fisher (1998) noted that the permeability of oceanic crust varies extensively due to the presence of fractures, and cannot simply be determined from core measurements.…”
Section: Comparison With a Hydrological Model And Other Oceanic Drillcontrasting
confidence: 59%
“…The maximum depth of thermal cracks grows with the cooling of oceanic lithosphere, and it can reach >20 km depth at 50‐Ma‐old lithosphere (Korenaga, 2007). The pervasive existence of thermal cracks in the oceanic lithosphere has some observational support as well (Chesley et al., 2019; Korenaga, 2017; Korenaga & Korenaga, 2016); we also note that the V p / V s ratio observed for the oceanic crust part of the Hatton Bank transect (Eccles et al., 2011) is consistent with the prediction of crack‐like porosity (Korenaga, 2017). Thus, a positive correlation between crustal velocity and thickness may simply result from the closure of porosities at greater pressures (see, e.g., Figure 14 of Behn & Kelemen, 2003 and related references), especially when oceanic crustal thickness is not very different from the standard value of 7 km (White et al., 1992); note that, with thermal gradient fixed, thicker crust leads to higher average temperature, which acts to reduce crustal velocity, but this effect is small (only 0.025 km s −1 difference between crustal thicknesses of 5 and 10 km) because of a counteracting pressure effect on seismic wave speed (White & McKenzie, 1989).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, for example, Naif et al (2013) used MT data to detect enhanced conductivity in the plate‐motion direction for partial melts at the LAB, interpreted as shearing. Chesley et al (2019) observed a similar anisotropy in subsolidus lithospheric mantle using a related electrical method (controlled‐source sounding), and Wang et al (2020) estimated melt fraction at the LAB beneath Mid‐Atlantic Ridge using MT data.…”
Section: Recent Observational Constraints On the Depth And Sharpness mentioning
confidence: 94%